Implementation of Strategies in Shaping Effective and Superior Schools (Multisite Study at SMP Islam al-Azhaar Tulungagung and SMP Negeri 1 Tulungagung) - Tri Prasetyo Utomo; Imam Saerozi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Implementation of strategies informing effective schools is a follow-up to the process of formulating strategies (planning) by various parties responsible for the process of effective school development. The implementation of the strategy is an action to achieve the educational objectives (effective schools) through the stages that have been set in the form of program structure, budget, operational standards, supervision, and evaluation. This research explore in-depth the implementation of strategies in Junior High School (SMP) Islam al-Azhaar Tulungagung and Junior High School (SMP) Negeri 1 Tulungagung. This research uses qualitative research methods, using phenomenological field studies. Meanwhile, data collection techniques are conducted through in-depth interviews, observations, and passive participants in the field as well as using other literature relevant to the concept of implementing strategies informing effective schools. The results showed that the implementation of strategies in shaping schools was effectively carried out through internal processes and external processes. This process will result in effective learning, effective teaching, and a conducive environment.